2019
DOI: 10.15171/ps.2019.40
|View full text |Cite
|
Sign up to set email alerts
|

The Improvement Effects of Gordonia bronchialis on Male Fertility of Rats with Diabetes Mellitus Induced by Streptozotocin

Abstract: Background: This study evaluated the possible protective effects of Gordonia bronchialis (Gb) on oxidative stress and some subsequent alterations on testis from rats undergoing an experimentally induced type 1 diabetes. Methods: A total of 40 male rats were randomly divided into four groups of ten. Diabetes was induced by injection of 55 mg/kg streptozotocin in 30 rats. Oral administration of Gb at dose of 105 (low dose) and 107 (high dose) CFU/rat was performed in two groups continuously for 14 days. The thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…They also reported that testicular morphology of diabetic rats significantly was improved on days 14 and 21 after the intervention. 1 It should be noted that these findings might be affected by the quality and reproducibility of experimental design mainly the time of study and sample size used in each of the studied time points. Diabetes is now one of the most challenging public health issues of our time.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…They also reported that testicular morphology of diabetic rats significantly was improved on days 14 and 21 after the intervention. 1 It should be noted that these findings might be affected by the quality and reproducibility of experimental design mainly the time of study and sample size used in each of the studied time points. Diabetes is now one of the most challenging public health issues of our time.…”
mentioning
confidence: 99%
“…We read with interest a recently published article in Pharmaceutical Sciences by Khordadmehr et al, titled "The improvement effects of Gordonia bronchialis on male fertility of rats with diabetes mellitus induced by Streprozotocin". 1 They found that 14 days administration of Gordonia bronchialis could effectively alleviate blood glucose, tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), malondialdehyde (MDA) and improve insulin, superoxide dismutase (SOD) and catalase (CAT) activities in diabetic rats. They also reported that testicular morphology of diabetic rats significantly was improved on days 14 and 21 after the intervention.…”
mentioning
confidence: 99%
See 1 more Smart Citation